PENINGKATAN PENGETAHUAN DANKETERAMPILAN PEMANFAATAN MEDIA SOSIAL UNTUK BRANDING DESA WISATA - Neng Virly Apriliyani; Mulil Khaira; Fitriah, Maria; Ginung Pratidina; Muhammad Encep; Desi Hasbiyah; Ruhimat; Cecep Wahyudin; Agustini; Dedy Ardiansyah Ramadhan; Sitti Sakinah; Tia Agustiani; Rafael Nuansa Ramadhan; Akmal Fadilah (Universitas Djuanda, 2023)
People are increasingly interested in visiting tourist attractions, including nature tourism. Thus, it is urgently needed to be innovative in promoting it with tourism village branding. The potential of a tourist village can boost the economy of local residents whose marketing can reach foreign countries. Social media can be used by the community to develop their business, one of which is by increasing branding. Community service methods use preparation, observation, counseling, training, pre-test and post-test. The results obtained show an increase in knowledge about environmental changes causing a change in the marketing system from 30% to 60%, knowledge of consumer characteristics from 24% to 43.33%, knowledge of consumer culture from 56% to 67%, knowledge of matters affecting consumer purchases from 56% to 66%, knowledge about telling experiences using products from 33.33% to 50%, knowledge about the function of campaigns on social media in building branding from 70% to 83%, knowledge about the # symbol on social media to mark topics from 67 % to 73%, knowledge about the use of captions on Instagram from 86% to 97%, the presence of subscriber features from 76% to 87%. The recapitulation shows an increase in knowledge and skills in using social media for tourism branding in Kabandungan Village from 56.43% to 70.93%. Keywords: social media, branding, tourism village